Combination of electrocoagulation with advanced oxidation processes for the treatment of distillery industrial effluent - Abdul Raman, Abdul Aziz; Asaithambi, P.; Daud, Wan Mohd Ashri Wan (Institution of Chemical Engineers, 2016)
The treatment of distillery industrial effluent by means various combinations of electrocoagulation with Advanced Oxidation Processes (AOPs) such as ozonation, electrocoagulation, peroxi-electrocoagulation, photo-electrocoagulation, ozone-electrocoagulation and peroxi-photo-electrocoagulation process on the removal of percentage color, COD and energy consumption. The effects of various operating parameters such as ozone flow rate (5 to 15 LPM), initial effluent pH (2 to 10), current density (0.10 to 0.50 A/dm2) and H2O2 concentration (50 to 500 mg/L) on the removal of pollutant were studied in this study. Moreover comparison of all the processes in terms of color removal, COD removal and energy consumption was also carried out. The experimental results showed that100% of color and COD removal could be achieved by ozone-electrocoagulation process with an energy consumption of 5.7 kW h/m3 within four hours of reaction time. The extent of color and COD removal was analyzed using a UV/vis spectrophotometer and closed reflux method.